PENGARUH PENERAPAN METODE KOOPERATIF TIPE TEAMS GAME TOURNAMENT TERHADAP HASIL BELAJAR GEOGRAFI KELAS X SMA NEGERI 3 GUNUNGSITOLI - Christian Anugerah Fajar Putra Zebua; Syafri Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine how the effect of the Application of Teams Game Tournament Type Cooperative Method on Geography Learning Outcomes of Class X SMA Negeri 3 Gunungsitoli. This research uses the Quasy Experiment method with a quantitative approach and this research design uses Pre-test - Post-test Control Group Design. The research sample was class X students of SMA Negeri 3 Gunungsitoli in the 2024/2025 academic year with a total of 351 students from 10 classes. The research sample consisted of class X-5 as the control class and class X-1 as the experimental class which was selected using purposive sampling technique. Data collection techniques include observation, documentation, and tests. The results showed that the average Pre-test of the experimental class was 58.03 and Post-test 87.14, while the control class obtained Pretest 61.65 and Post-test 72.09. There was a significant increase in the experimental class. The results of the Paired Sample T-Test test showed a significance level (sig) of 0.001. Because this significance value is smaller than 0.05, Ho is rejected and Ha is accepted.